A Computational Fluid Dynamics Investigation of a Novel Ducted Winglet Design - RICHARD DAVIS (2023)
Induced drag is a crucial component of the total drag experienced by aircraft,and reducing it can improve their performance. This study investigates theefficacy of a novel ducted wingtip device in reducing induced drag.Computational fluid dynamics simulations were performed on an EmbraerERJ145 aircraft with different wingtip configurations, including a ductedwinglet, a conventional winglet, and a standard wingtip, across a range of anglesof attack. Post-processing techniques such as flow visualization and Trefftzplane analysis were employed to examine the performance of the differentwingtip configurations and their induced drag.Results show that the ducted winglet configuration produced lower values of thecoefficient of induced drag across all angles of attack when compared to boththe conventional winglet and standard wingtip. However, it also incurred higherform drag penalties due to eddying and separation behaviour identified at theduct. While the ducted winglet produced similar results for the coefficient oftotal drag at 0 and 1 degree angle of attack compared to both the conventionalwinglet and standard wingtip, it resulted in higher values at 3, 4, and 5 degreesangle of attack.Overall, the study suggests that the design of the ducted winglet can reduceinduced drag and improve aircraft performance. However, further improvementsto the design are necessary to address form drag penalties and enhance itsefficacy.